Discussion of An Explanation for Accounting Income Smoothing - Newman, Paul (Journal of Accounting Research, 1988)
Paul Newman, Discussion of An Explanation for Accounting Income Smoothing, Journal of Accounting Research, Vol. 26, Studies on Management's Ability and Incentives to Affect the Timing and Magnitude of Accounting Accruals (1988), pp. 140-143